충진밀도와 여과속도가 섬유사 여과기의 처리 성능에 미치는 영향 - 임정훈(Jeong Hoon Im); 김효관(Hyo Kwan Kim); 이정준(Jung June Lee); 문태섭(Tae Sup Moon); 정민기(Min Ki Jeong); 우혜진(Hae Jin Woo); 김창원(Chang Won Kim) (Daehan hwan'gyeong gonghag hoeji, 2006)
A flexile fiber filter developed in Korea was operated to evaluate the effect of packing density and filtration velocity on particle removal. The pilot-scale fiber filter with 40 cm of diameter and 2 m of height was packed with polyamide fibers of which mean diameter was approximately 0.93 mm. While the filtration velocity was maintained at 325 m/hr, the particle removal efficiency was compared with various of packing density from $70kg/m^3\;to\;100kg/m^3$. On the contrary, when the packing density was maintained at $70kg/m^3$, the particle removal efficiency was examined with various filtration velocity from 65 m/hr to 400 m/hr. The filtration pressure increased with the packing-density increase. Below $80kg/m^3$ of packing density, the removal efficiencies of turbidity ad SS were less than 30% and 50%, respectively. At $100kg/m^3$ of packing density, the removal efficiencies of them were nearly 45% and 60% respectively. The filtration pressure increased with the filtration-velocity increase. A better removal efficiency was obtained at a lower filtration velocity, removal efficiency of them were 73% at 65 m/hr. Consequently, The filtration velocity was the more important factor to enhance the particle removal efficiency compared with the packing density in fiber filter. 본 연구에서는 국내에서 개발되어진 섬유사 필터의 충진밀도와 여과속도가 처리 효율에 미치는 영향에 대한 연구결과를 나타내었다. 0.93 mm의 직경을 가진 폴리아마이드 섬유사가 충진된 직경 40 cm, 높이 2 m의 pilot-scale 규모의 반응기에서 수행되었다. 충진밀도가 섬유사 여과기의 처리효율에 미치는 영향을 살펴보기 위해 여과속도를 325 m/hr로 고정하고 충진밀도를 $70kg/m^3$에서 $100kg/m^3$의 범위에서 운전하였으며, 이와 반대로 여과 속도가 섬유사 여과기의 처리효율에 미치는 영향을 연구하기 위해서 충진밀도를 $70kg/m^3$으로 고정시킨 뒤 여과속도를 65 m/hr에서 400 m/hr의 범위로 운전하였다. 충진밀도가 증가할수록 여과 압력은 기하급수적으로 증가하였다. 탁도 및 SS 제거효율은 $80kg/m^3$까지는 30% 이내의 낮은 제거효율을 나타내었으며, $100kg/m^3$에서도 50% 이하의 낮은 제거효율을 나타내었다. 여과속도에 따른 섬유사 여과기의 여과압력은 여과 속도와 비례적으로 증가하였다. 여과속도가 낮을수록 탁도와 SS의 제거효율도 증가하였으며 65 m/hr에서 73%의 제거 효율을 나타내었다. 전체적으로, 섬유사 여과기를 이용한 입자상 물질의 제거 효율을 개선하기 위해서는 충진 밀도 보다 여과속도를 유입수 특성에 따라 적절히 조절하는 것이 효과적인 것으로 나타났다.